Analisis Terhadap Pembuatan Surat Pernyataan Keabsahan dan Kebenaran Dokumen Elektronik Pada Sertifikat Hak Tanggungan - Sitompul, Gabriel Amadeus; Siahaan, Albert Lodewyk Sentosa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to find out how the validity and correctness of electronic documents issued by PPAT and to find out how legal protection against PPAT as the person responsible for the validity and correctness of electronic documents. The type of research that will be used in this research is descriptive normative legal research. The type of data used in the research is qualitative data. The data sources used in this research are secondary data sources. The data collection technique used in this research is using secondary data with the library material method. The approach used in this research is a statutory approach. Literature study (library research) is the study of written information about the law that comes from various sources and can be widely published and is needed in normative legal research. The research approach used in this thesis research is qualitative research. This thesis research uses descriptive analysis techniques where the use of qualitative approaches to secondary data. The results showed that the statement of validity and correctness of electronic documents issued by PPAT is valid and must be the responsibility of PPAT based on the provisions of Article 10 paragraph (4) of the Government Regulation on Agrarian and Spatial Planning or the National Land Agency Number 5 of 2020 and legal protection for PPAT is limited to formal responsibility only. PPAT is not responsible in the event of falsification of documents provided by the client.